Fixed Points of Set-Valued Mappings under Generalized Contractive Conditions in Ordered Metric Spaces: Hemant Kumar Nashine, Zoran Kadelburg - Team, Support (Thai Journal of Mathematics, 2017)
In the present work we establish some new xed point theorems for a set-valued operator satisfying generalized contractive condition in a partially ordered complete metric space. Thereafter we present common xed point results for a pair of weakly isotone increasing set-valued mappings. Finally, some examples are given to illustrate the usability of our results, also showing that the use of order can be crucial.